If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2x + 9) = -8 Reorder the terms: -8(9 + 2x) = -8 (9 * -8 + 2x * -8) = -8 (-72 + -16x) = -8 Solving -72 + -16x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + -16x = -8 + 72 Combine like terms: -72 + 72 = 0 0 + -16x = -8 + 72 -16x = -8 + 72 Combine like terms: -8 + 72 = 64 -16x = 64 Divide each side by '-16'. x = -4 Simplifying x = -4
| 4z^2-9x+2=0 | | i^2-50z=0 | | 12x+8=5x+36 | | 5(x-1)=-35 | | z^2-50i=0 | | -0.7c=-16.1 | | 10(x-6)=-147 | | 15-x^2=3x+5 | | 9x-2.3x-3=0 | | 9.7-m=2.8 | | 9-.5x=2 | | 6(x+1)=-18 | | 9-3x=-6x+3 | | 9x+6=3(2-x) | | 5x+2+5x+1=30 | | 6-5x=-x-2 | | x+5*3=36 | | -3(3x-7)=5(3x+1) | | 3(3x-7)=5(3x+1) | | 3(3x+6)=135 | | 8(2x+9)=120 | | .66x-4=-1 | | 6y+6=y-2 | | 1g(x+7)+1g(3x+1)=2 | | (-2)=4x+2 | | (x-3)*7=70 | | 0.05x=150 | | .66x-4=1 | | -4x+9x-(-4)=12x-5-(-10) | | 4y(5y-8)+24y= | | (x-10)*4=24 | | 2(4x-5)=12 |